2023
DOI: 10.1071/hc22147
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing for sexually transmitted infections in Aotearoa New Zealand: a review of clinician-notified gonorrhoea and syphilis data

Abstract: Introduction. The sexually transmitted infections (STIs) gonorrhoea and syphilis became notifiable in Aotearoa New Zealand in 2017, requiring diagnosing clinicians to complete an anonymous case report form detailing behavioural, clinical and management information. Surveillance for gonorrhoea occurs through laboratory and clinician notification, whereas syphilis is only cliniciannotified. Aim. To review information related to contact tracing (partner notification) from routinely collected gonorrhoea and syphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, a review of surveillance data has found that contact tracing was recorded as 'planned' or initiated' for only about 80% of cases, with the actual outcomes unknown. 4 For 20% of syphilis and 16% of gonorrhoea cases, contract tracing was not possible because the contacts were anonymous.Another STI is the Human Papillomavirus (HPV), with most of cervical cancer now known to be caused by preceding infections of certain HPV subtypes. Cervical screening is switching from cervical cytology to HPV testing, which can be done with vaginal selfswabs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a review of surveillance data has found that contact tracing was recorded as 'planned' or initiated' for only about 80% of cases, with the actual outcomes unknown. 4 For 20% of syphilis and 16% of gonorrhoea cases, contract tracing was not possible because the contacts were anonymous.Another STI is the Human Papillomavirus (HPV), with most of cervical cancer now known to be caused by preceding infections of certain HPV subtypes. Cervical screening is switching from cervical cytology to HPV testing, which can be done with vaginal selfswabs.…”
mentioning
confidence: 99%
“…However, a review of surveillance data has found that contact tracing was recorded as 'planned' or initiated' for only about 80% of cases, with the actual outcomes unknown. 4 For 20% of syphilis and 16% of gonorrhoea cases, contract tracing was not possible because the contacts were anonymous.…”
mentioning
confidence: 99%